2022
DOI: 10.3390/ijms232213700
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Changes in Saliva and Serum Proteins of Pigs with Meningitis Caused by Streptococcus Suis: A Proteomic Approach

Abstract: Meningitis due to Streptococcus suis causes high mortality and morbidity on pig farms and has increasing zoonotic potential worldwide. Saliva proteome analysis would potentially be useful in elucidating pathophysiological changes and mining for new biomarkers to diagnose and monitor S. suis infection. The objective of this study was to investigate the changes in the salivary and serum proteome profile of piglets with meningitis. The LC-MS/MS TMT proteomic approach was used to analyze saliva and serum samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
(72 reference statements)
2
11
1
Order By: Relevance
“…In addition, it has been described to capture bacterial siderophores produced by pathogenic bacteria, such as E. coli and, indeed, Lcn2-deficient mice are prone to infection and sepsis [ 16 ]. Although in our study LCN increased, in a previous report it was observed a decrease of LCN in the saliva of pigs with Streptococcus suis infection [ 4 ]. Further studies should be undertaken to elucidate the mechanisms involved in the change in LCN since in some cases, such as in the Streptococcus suis infection, the decrease of lipocalin could indicate a high susceptibility to worsening sepsis [ 4 ].…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…In addition, it has been described to capture bacterial siderophores produced by pathogenic bacteria, such as E. coli and, indeed, Lcn2-deficient mice are prone to infection and sepsis [ 16 ]. Although in our study LCN increased, in a previous report it was observed a decrease of LCN in the saliva of pigs with Streptococcus suis infection [ 4 ]. Further studies should be undertaken to elucidate the mechanisms involved in the change in LCN since in some cases, such as in the Streptococcus suis infection, the decrease of lipocalin could indicate a high susceptibility to worsening sepsis [ 4 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Overall, in our report, we found changes in proteins in saliva related to inflammation and the immune system, as have been described in saliva in pigs with sepsis experimentally induced by LPS administration and other infectious diseases such as S. suis infection [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Streptococcus suis is the most important bacterial agent that causes meningitis in pigs. Disease caused by S. suis is more prevalent in nursery pigs, but sucklers and young fatteners can also be affected [ 109 , 110 ]. The ability of several pathogenic microorganisms to form biofilms on host surfaces contributes to their virulence, and recent studies have found that S. suis can protect itself by forming biofilms, since the ability of bacteria to attach and colonize host tissues is a critical step in the initiation of infection, leading to increased drug resistance and prolonged disease [ 80 , 111 ].…”
Section: Current Understanding Of Biofilm Formation In Animal Diseasesmentioning
confidence: 99%